Use of biostimulant in the initial development of watermelon in saline soil (Research, Society and Development, 2020)
The use of biostimulants has been used as a new technology that provides the attenuation of salt stress in plants, as well as a greater increase in plant production. The objective of this research was to evaluate the tolerance and initial development of the Crinson Sweet watermelon submitted to applications of the biostimulant VIUSID-AGRO, grown in saline soil. Five treatments were tested: Soil salinity of 0.6 dS m-1 Without Biostimulant (SS0.6 + SB); Soil salinity of 0.6 dS m-1 and biostimulant (SS0.6 + BVA); Soil salinity of 1.6 dS m-1 and Biostimulant (SS1.6 + BVA); Soil salinity of 2.6 dS m-1 and Biostimulant (SS2.6 + BVA) and Soil salinity of 3.6 dS m-1 and Biostimulant (SS3.6 + BVA), with 4 repetitions. The application of biostimulant in plants subjected to salinity of 3.6 dSm-1 favored, mainly the number of leaves, fresh stem mass, dry stem mass, total fresh mass, percentage of dry mass, partition of dry leaf mass and partition of the dry stem mass. The SS2,6 + BVA treatment increases the leaf number, root volume, stem dry mass, root dry mass and total fresh mass of the watermelon plants, while the SS0,6 + BVA treatment increases the number of leaves, total fresh weight, leaf dry weight, root dry weight and total dry weight. The presence of the biostimulant in plants submitted to salinity of 1.6 dS m-1 favored the variables: plant length, number of leaves, dry stem weight and total fresh weight.